Representatif Kolonialisme dalam Novel Laskar Pelangi Karya Andrea Hirata: Pendekatan Sosiologi Sastra dan Teori Postkolonialisme - Azzahra, Ratna; Nurholis, Nurholis (CV. Eduartpia Publisher, 2023)
This research applies qualitative research methods with a sociological literary approach supported by postcolonialism theory to analyze the novel